Assessment of local residents’ perception of the language situation in the Republic of Tuva (based on the findings of a 2021 field study) - Kaplunova, Maria Ya. (The New Research of Tuva, 2022)
The linguistic situation in the Republic of Tuva is traditionally determined by the co-functioning of the Tuvan language of the titular nation and the nationwide Russian language as the language of interethnic communication. At the same time, despite the obvious numerical superiority of the Tuvans (more than 80% of the population of Tuva), over the past decade there has been a steady linguistic shift towards Russian in the Republic. This fact causes concern among linguists and ethnographers. The article provides an analysis of the current situation in the region as perceived by residents of the capital of the Republic of Tuva, Kyzyl. The language shift is already considered as a fact of life there. A field study (a series of interviews with 25 respondents) was conducted in July 2021 in Kyzyl. The opinions presented in the article testify to the intensity of the language shift process both in the city of Kyzyl and in other parts of the Republic of Tuva. Most informants expressed deep concern about the low level of the functional development of the Tuvan language in the region and the mass shift to the Russian language among the Tuvans. This is especially evident because of the low or zero level of proficiency in Tuvan among preschoolers and younger schoolchildren as well as amid a decrease in the level of literacy among the native Tuvan speakers. Most informants admit that if the current situation persists, the Tuvan language may gradually become extinct, though this process is still reversible. According to the informants, the prospects for the preservation and revival of the Tuvan language among the population of Tuva consist in enhancing its stature among the population through state support as well as through the spread of Tuvan culture.